Analisis Perpindahan Konsumen pada Kedai Kopi Kaki Lima Menggunakan Metode Markov Chain (Studi Kasus: T-Razz Coffee) - Isa, Nurfadillah Rahmadaniyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of coffee shop businesses in Gorontalo has intensified competition among business operators, including street-side coffee stalls. This condition provides consumers with more alternatives in choosing places to enjoy coffee and potentially leads to customer switching between coffee shops. This study aims to analyze the pattern of customer switching between T-Razz Coffee and other street-side coffee stalls in the Center Point area, Bone Bolango Regency. This research employs a quantitative approach using the Markov Chain method. The results of the Markov analysis indicate a steady state condition, with the market share of T-Razz Coffee reaching 61.07%, while other street-side coffee stalls account for 38.92%. These findings provide an overview of customer switching patterns that may serve as a basis for strategic considerations in responding to competition within the coffee shop industry.